Peningkatan Hasil Belajar TIK Melalui Model Pembelajaran Think-Pair-Share Dengan Camtasia Studio Pada Siswa - Wardoyo Wardoyo (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
This study aims to determine objectively about the improvement of learning outcomes in Information and Communication Technology (ICT) through the Think-Pair-Share (TPS) model with Camtasia Studio in class VIII junior high school students. The method used in this research is the classroom action research method according to Mc Taggart, R and Kemmis, S which consists of 4 stages, namely planning, action, observation and reflection. The procedure is carried out in the form of a cycle that lasts two cycles with each cycle consisting of 2 meetings. Data presentation was carried out by means of quantitative analysis which was measured based on a written test conducted at the end of each cycle. The results showed that quantitatively there was an increase in ICT learning outcomes after the application of the Think-Pair-Share (TPS) model with Camtasia Studio, namely the increase in: (a) The average from cycle 1 = 83.91 to = 89.35 in the cycle 2, or there is an increase of 5.43 values; (b) The number of students who scored ≥ 75 (KKM = 75): from cycle 1 = 78.26% to 100% in cycle 2, or an increase of 21.74%.